Highest weights, projective geometry, and the classical limit: I. Geometrical aspects and the classical limit - Hannabuss, K.C. (Journal of geometry and physics, 2000)
This paper starts with a new proof that highest weight vectors for semi-simple Lie group representations can be characterised by quadratic equations, and finds the automorphism group of this quadratic variety. The idea is illustrated by various geometrical examples. Various generalisations to Clifford algebras and quantum groups are explored, as well as the relationship between geometry, second quantisation, and the classical limit.